An Actor''s Guide to Getting Work. - Dunmore, Simon (Bloomsbury Publishing, 2012)
''Essential reading for any young actor'' Dame Maggie Smith Competition for acting work is fierce and talent is not necessarily enough. Actors need all the help they can get with all aspects of the profession. Now in its fifth edition, completely revised and updated, this practical, comprehensive guide contains invaluable information and advice to enable actors to succeed in the business. Written with honesty, humour and thoroughness, An Actor''s Guide to Getting Work draws on the author''s rich experience in the field to offer advice to both the novice and the seasoned performer. New material.